2003
DOI: 10.1037/0022-006x.71.5.910
|View full text |Cite
|
Sign up to set email alerts
|

An Internet intervention as adjunctive therapy for pediatric encopresis.

Abstract: This study evaluated the benefits of enhanced toilet training delivered through the Internet for children with encopresis. Twenty-four children with encopresis were randomly assigned to the Internet intervention group (Web) or no Internet intervention group (No-Web). All participants continued to receive routine care from their primary care physician. The Web participants demonstrated greater improvements in terms of reduced fecal soiling, increased defecation in the toilet, and increased unprompted trips to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
7

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 16 publications
3
108
0
7
Order By: Relevance
“…These results are very comparable to those from the previous face-to-face trial of family problem solving with families of children with TBI , suggesting that an on-line approach can be as successful as one delivered in person. These results are consistent with those of the other study that has implemented a family-centered intervention over the Web (Ritterband et al, 2003). It is noteworthy that virtually all participants with prior psychotherapy experience in the present project reported that FPS was more helpful than prior experiences with psychotherapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are very comparable to those from the previous face-to-face trial of family problem solving with families of children with TBI , suggesting that an on-line approach can be as successful as one delivered in person. These results are consistent with those of the other study that has implemented a family-centered intervention over the Web (Ritterband et al, 2003). It is noteworthy that virtually all participants with prior psychotherapy experience in the present project reported that FPS was more helpful than prior experiences with psychotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…On-line or computer-mediated approaches have not been widely used with families, although existing stud-ies indicate considerable potential (Glueckauf et al, 2002;Ritterband et al, 2003). Glueckauf and colleagues reported that home-based family videoconferencing, phone conferencing, and face-to-face meetings were equally effective in reducing the frequency and severity of problem behaviors in teenagers with epilepsy.…”
Section: Emerging Technologies and On-line Therapeutic Interventionsmentioning
confidence: 99%
“…5 On the Web page, users read the following instructions: "We hope you find the information in this website to be helpful. Before you can begin, please enter the ID number you were given in the space below, and then click the button to begin."…”
Section: Web Sitementioning
confidence: 99%
“…В итоге поведенческая терапия уси-ливает мотивацию, предусматривает систему поощрения, таким образом, приучая ребенка не избегать посещения туалета. Такой подход в сочетании с приемом слабительных средств снижает частоту каломазания (недержания кала), увеличивает число актов дефекации в туалете и частоту самопроизвольных посещений туалета [33].…”
Section: группа сравненияunclassified